Ice/Salt‐Assisted Synthesis of Ultrathin Two‐Dimensional Micro/Mesoporous Iron and Nitrogen Co‐Doped Carbon as an Efficient Electrocatalyst for Oxygen Reduction. Issue 22 (21st March 2019) - Li, Hanyu; Zhang, Zhengping; Iyoda, Tomokazu; Dou, Meiling; Wang, Feng
Abstract: An ice/salt‐assisted strategy has been developed to achieve the green and efficient synthesis of ultrathin two‐dimensional (2D) micro/mesoporous carbon nanosheets (CNS) with the dominant active moieties of Fe−N4 (Fe‐N‐CNS) as high‐performance electrocatalysts for the oxygen reduction reaction (ORR). The strategy involves freeze‐drying a mixture of iron porphyrin and KCl salt using ice as template followed by a confined pyrolysis with KCl as an independent sealed nanoreactor to facilitate the formation of 2D carbon nanosheets, N incorporation, and porosity creation. The well‐defined assembly of ultrathin 2D carbon nanosheets ensures high utilization of D1 and D3 Fe−N4 active sites, and effectively promotes the mass transport of ORR reactants by virtue of the pronounced mesoporous structure. The resulting Fe‐N‐CNS electrocatalyst was shown to exhibit superior ORR activity, better electrochemical durability, and methanol tolerance towards ORR in alkaline electrolyte relative to the commercial Pt/C electrocatalyst. Abstract : Cool idea ! A high‐performance Fe−N4 electrocatalyst was prepared by means of an ice/salt‐assisted strategy. It was shown to exhibit superior activity in the oxygen reduction reaction (ORR), better electrochemical durability, and improved methanol tolerance towards ORR in alkaline electrolyte than commercial Pt/C electrocatalyst (see figure).